Aprendizagem organizacional no processo de desenvolvimento de produtos: investigação do conhecimento declarativo no contexto da sistemática de satage-gates. - Silva, Mariana Maciel da (2003)
The companies inserted in the current dynamic context have discovered different ways to accomplish their activities and manage their processes. Regarding to NPD (New Product Development) process, it is possible to observe the adoption by companies of practices that enable better performance, efficient results and the continuous improvement of the process. The Stage-gates systematic can be considered as an example of these practices. This systematic divides the NPD in Stages interchanged by review and decision points, named gates. The gates goals are to evaluate accomplished activities, of which scope must be aligned to business strategy, and to decide if the condition of the process is to continue, to be postponed, to be recycled or even to be cancelled. Moreover, this systematic allows to structure moments to analyze the NPD process performance and manage continuous improvement, factors linked to creation and improvement of NPD process competences, that is, to learning organizational competences. The purpose of this work is to list the existing and explicit activities in the context of product development projects, and to discuss their association to the elements of the Declarative Knowledge of Organizational Learning. The research method was the case study, with characteristics of qualitative and descriptive analysis. The case was conducted in a Brazilian business unit of a multinational automotive company, through visits in order to follow some meetings and to interview people involved in the studied projects. The results of this work are the description and analysis of existing activities in NDP process that can be associated to the elements of Declarative Knowledge of Organizational Learning in the cross-team and within-team learning environment. Many practices, in the studied company, are almost ready to be used as learning activities addressed by Declarative Knowledge elements such as registering, reviewing, relating, keeping and sharing. These elements are presented in the company, especially in technical activities, but it is a matter of conscience to use them as improvement opportunities during the development process management.